Audit of management of eclampsia and severe pre-eclampsia against RCOG standards. (7th June 2011) - Reiley, J; Moss, H; Gibson, J
Abstract : Introduction: Confidential enquiries into maternal deaths show substandard care in a significant percentage of the deaths from eclampsia.1 The RCOG Green Top Guideline No 10(A) (2006)2 makes recommendations to standardise the approach of the management of severe pre-eclampsia/eclampsia to improve outcomes. Aim: To evaluate the management of women presenting with severe pre-eclampsia and eclampsia to any of our 4 regional maternity units against the RCOG guideline.2 Method: A 1 year retrospective audit. Results: 78/80 identified cases were available for analysis. Two pregnancies resulted in stillbirth. The mean gestation at delivery was 35+0 (range 26+2 to 40+3). Diagnosis: The average number of blood pressure readings was 3 per patient, all had appropriate blood tests performed, quantification of proteinuria was made primarily by dipstick testing. Therapy: Labetalol was used in 65 cases (88%) including 5/8 asthmatics. 39 (55%) with severe pre-eclampsia and all with eclampsia received magnesium sulphate. The majority received a 4 g loading and 1 g/h maintenance dose. There were no recurrent seizures. Fluid restriction was evident antenatally/intrapartum in 55% and postpartum in 67%. Consultant obstetricians reviewed 75 patients within 24 h of diagnosis. Senior anaesthetic input was significantly less (50%). Fetal assessment/preparation: All (viable) had CTGs performed. All deliveries more than 48 h after diagnosis had ultrasound assessment of the fetus performed. 23 women delivered a live birth before 34 weeks gestation, all received steroids. Conclusions: Management of a well known complication still requires improvements. A region wide guideline has been devised to direct therapy, improved fluid balance and facilitate comprehensive multidisciplinary care.